NATURE:: MITOLOGI HARIARA SUNDUNG DI LANGIT UNTUK KEBERLANJUTAN ALAM DI MASYARAKAT BATAK TOBA - Sianipar, Ruth Ananda; Marpaung, Frans Best Soma; Sianipar, Herna (STT-RAI Batam, 2025)
Abstract The issue of environmental degradation has become a global concern, affecting various regions worldwide, including the Batak Toba community. Numerous efforts have been made to mitigate the worsening damage. This paper aims to explore moral values through Batak Toba local wisdom as a solution to environmental destruction. One approach is by instilling respect for trees. In Batak Toba mythology, Hariara Sundung di Langit is known as a sacred tree with profound symbolic meaning. The values embodied in this tree can be utilized to address environmental damage. This study employs a qualitative research method with a phenomenological approach to explore the social ideas behind the meaning of Hariara Sundung di Langit, which is protected and nurtured by the Batak Toba community. The protection and preservation of Hariara Sundung di Langit can be applied as a step toward sustainable environmental conservation. This gives rise to the concept of Na Ture, an invitation to preserve a good and harmonious environment based on the Batak Toba worldview.